Demographic and Clinical Correlates of Narcolepsy in Adolescents Hospitalized with Mood Disorders: A Nationwide Inpatient Sample (NIS) Study. Issue 3 (4th May 2023) - Patel, Rikinkumar S.; Veluri, Nikhila; Chopra, Amit
ABSTRACT: Objectives: To discern the differences in demographic, clinical comorbidities, and hospital outcomes associated with narcolepsy in adolescents hospitalized for mood disorders. Methods: We included 639, 064 adolescents hospitalized with mood disorders, that is, major depressive disorder (MDD) and bipolar disorders (BP) from the nationwide inpatient sample. About 0.04% of inpatients had comorbid narcolepsy (N = 267) and we extracted a demographically matched control group (N = 270) for comparison. Results: Mood-disordered adolescents with narcolepsy had a higher prevalence of comorbid obesity (18.5% in BP, 14.4% in MDD) and sleep apnea (9.3% in BP, 9.6% in MDD) compared to those without narcolepsy. Obesity and sleep apnea were significantly more prevalent in Black adolescents hospitalized for MDD and BP (P < .001). There was a higher percentage of females with BP and comorbid narcolepsy than males (59.9% vs 40.1%). In comparison, MDD and comorbid narcolepsy were observed more in males (57.1% vs 42.9%). Conclusions: Our study results suggest a significantly higher prevalence of obesity and sleep apnea comorbidity in mood-disordered adolescents with narcolepsy with an overall negative impact on hospital outcomes.